2015
DOI: 10.1111/jam.12782
|View full text |Cite
|
Sign up to set email alerts
|

Application of lemongrass oil in vapour phase for the effective control of anthracnose of ‘Sekaki’ papaya

Abstract: The potential practical application of this technology can reduce reliance on synthetic fungicides for the control of postharvest diseases in papaya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 37 publications
2
32
0
1
Order By: Relevance
“…Therefore, biological control appears to be beneficial in reducing effects of witches' broom disease to economically viable levels and in decreasing the use of chemical fungicides that may cause collateral damage [6] .The chemical components occurring naturally in variety of plants in Brazilian ecosystems are a potential source of bioactive materials [20]. Plant metabolites and plant-based pesticides and fungicides increasingly appear to be a promising alternative to synthetic pesticides as their application promises minimal environmental impact [21,22]. Therefore, they are helpful for the development of effective products for pest control [23], including pathogenic fungi [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological control appears to be beneficial in reducing effects of witches' broom disease to economically viable levels and in decreasing the use of chemical fungicides that may cause collateral damage [6] .The chemical components occurring naturally in variety of plants in Brazilian ecosystems are a potential source of bioactive materials [20]. Plant metabolites and plant-based pesticides and fungicides increasingly appear to be a promising alternative to synthetic pesticides as their application promises minimal environmental impact [21,22]. Therefore, they are helpful for the development of effective products for pest control [23], including pathogenic fungi [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The propolis extract coatings showed lower permeability to water vapor between the fruit and the medium until the 18 th day of storage, thereby reducing the weight loss of oranges. Ali et al (2015b) also observed an highest percentage weight (19.1%) in peppers coated with ethanol under refrigeration conditions at 13°C and RH 90%, while control fruits and coated with 1% and 5% ethanolic extract propolis did not differ (17.2, 18 and 16.85%, respectively). However, pitaya coated with 0.5% ethanol extract of propolis showed a 13% weight loss when stored at 20 ± 2°C and 80 ± 5% RH for 20 days of storage (Zahid et al, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…In a few years, propolis has also been evaluated to improve quality of coatings. The hydrophobic compounds of propolis, as waxes and essential oils, acts as a barrier to water vapor and gas exchange (Ali et al, 2015b(Ali et al, , 2014Carvalho et al, 2013;Zahid et al, 2013) and possess broad spectrum of antimicrobial activity (Ali et al, 2015b(Ali et al, , 2014.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…The disc diffusion method, however, may present a problem, as EOs are hydrophobic, and volatile components have low water solubility in media (Nedorostova et al, 2009;Tajkarimi et al, 2010). In contrast, the volatilisation method is considered suitable (Nedorostova et al, 2009;Ali et al, 2015;Perumal et al, 2016;Shahabi et al, 2017) for determining antimicrobial activity and obtaining minimal inhibitory concentration (MIC) or minimum bactericidal concentration (MBC), which represents the lowest concentration of EO required to inhibit target microorganisms (Dannenberg et al, 2016;Lu et al, 2016;Alejo-Armijo et al, 2017). The screening method is not standardised for comparing liquid and vapour phases of EO (Tyagi & Malik, 2011;Boukhatem et al, 2013).…”
Section: Introductionmentioning
confidence: 99%